The level of inflation as a solution to mitigate speculation on the increase of the minimum wage by 2025 - Andrade Rosas, Luis Antonio; Coronado González, Yaxk’in U Kan (Revista Internacional de Salarios Dignos, 2024)
The new government administration in Mexico is tasked with maintaining and improving the proposals of the previous administration. In this sense, we compare the proposed 20% increase in the minimum wage in the last year of the previous administration with the speculation of a 12% increase in the minimum wage by 2025. The above is analyzed based on a digital platform on wages, with which we estimated labor demand and supply for Mexico (2023). Based on these estimates, wage increases and inflation levels for 2024 and 2025 were incorporated. As part of the results, it is obtained that the 10% inflation level can counteract the speculative increase of 12% in the minimum wage for 2025; since, if the speculation of 12% for 2025 is left to act freely, the equilibrium wage would be 3% lower, since it does not consider real scenarios as reflected by an inflation level. Concerning the salary level obtained in equilibrium conditions for 2024, this was 10% lower than in 2023, because it did not consider inflationary scenarios. The paper calls on the authorities to involve both sides of this game: companies and workers, in order to determine such an important labor policy of great economic impact, as is the wage increase.